Keputusan Penggunaan QRIS Berdasarkan Pengaruh Persepsi Kemudahan dan Keamanan Melalui Persepsi Kepercayaan Pada GEN_Z di Tawangmangu - Dheya Patricia; Alexander Mario Retto Djong (Politeknik Ganesha Medan, 2026)
This study was conducted to analyze the impact of perceived ease of use and perceived security on the decision to use QRIS, with perceived trust as a mediating variable. The sample was taken using a purposive approach with the size determined using the hair formula. This study was conducted in Tawangmangu District using a quantitative approach and survey method. The questionnaire was distributed to 145 Gen Z participants who have experience using QRIS. This research is based on the Technology Acceptance Model (TAM) as its theoretical framework. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the aid of SmartPLS version 4 software to test the relationships between the variables in the model being studied. The research findings indicate that the perception of ease does not have a significant impact on the decision to use. Furthermore, the perception of security also does not have a significant impact on the decision to use. However, the perception of trust plays an important role, significantly influencing the decision to use. Moreover, ease of use significantly affects the decision through trust, while security also influences the decision to use through trust.